Knockdown of Sec16 causes early lethality and defective deposition of the protein Rp30 in the eggshell of the vector Rhodnius prolixus - Rios, Thamara; Bomfim, Larissa; Pereira, Jéssica; Miranda, Kildare; Majerowicz, David; Pane, Attilio; Ramos, Isabela (Frontiers in Cell and Developmental Biology, 2024)
In nearly every species of insect, embryonic development takes place outside of the mother's body and is entirely dependent on the elements that the mother had previously stored within the eggs. It is well known that the follicle cells (FCs) synthesize the eggshell (chorion) components during the process of choriogenesis, the final step of oogenesis before fertilization. These cells have developed a specialization in the massive production of chorion proteins, which are essential for the protection and survival of the embryo. Here, we investigate the function of Sec16, a protein crucial for the endoplasmic reticulum (ER) to Golgi traffic, in the oocyte development in the insect Rhodnius prolixus. We discovered that Sec16 is strongly expressed in vitellogenic females' ovaries, particularly in the choriogenic oocyte and it is mainly associated with the FCs. Silencing of Sec16 by RNAi caused a sharp decline in oviposition rates, F1 viability, and longevity in adult females. In the FCs, genes involved in the unfolded protein response (UPR), the ubiquitin-proteasome system (UPS), and autophagy were massively upregulated, whereas the mRNAs of Rp30 and Rp45 - which code for the two major chorion proteins - were downregulated as a result of Sec16 silencing, indicating general proteostasis disturbance. As a result, the outer surface ultrastructure of Sec16-silenced chorions was altered, with decreased thickness, dityrosine crosslinking, sulfur signals, and lower amounts of the chorion protein Rp30. These findings collectively demonstrate the critical role Sec16 plays in the proper functioning of the FCs, which impacts the synthesis and deposition of particular components of the chorion as well as the overall reproduction of this vector.